Estrategia pedagógica de interacción para vincular a las familias del grado tercero de la sede Antonio Nariño con la escuela mejorando la participación educativa en la institución Gustavo Uribe Ramírez (2017)
In this investigation, an intervention is made to the pedagogical process in which the teachers allow or don't allow the families of the third grade students of the Antonio Nariño headquarters to become involved with the school. This is the result of the project presented in the first semester of 2016 in Educational Cartography of the Master of Education of the University of Los Andes, Ramos, L and Rodríguez, M (2016), which allowed us to understand the relevance to identify the tensions that arise between the parents, students and teachers around the formative processes. It was then that we decided to propose a research exercise that would allow us to transform the means of interaction from our educational practice to involve the parents of the third grade students of Antonio Nariño...